Analisis Penggunaan Media Konkret pada Hasil Pembelajaran Matematika Materi Pecahan - Nur Latifa Az-Zahara; Mulya Mulawarni; Siti Nailatus Syifa; Een Unaenah (Journal Innovation In Education, 2025)
The use of concrete media in mathematics learning plays an important role in helping students understand abstract concepts, particularly fractions. Students often experience difficulties in understanding the concept of equivalent fractions due to abstract learning and a lack of connection to real-world experiences. This study aims to analyze the process of using concrete media in mathematics learning on equivalent fractions in fifth-grade elementary schools. This study uses a qualitative descriptive approach with data collection methods through observation and interviews with teachers and documentation of learning activities. The concrete media used in this study included origami paper, wafers, and pizza replicas, which were chosen because their shapes and properties allow students to carry out activities of dividing, cutting, and arranging parts according to the concept of fractions. The results of the study indicate that the use of concrete media not only functions as a visual aid but also provides a multisensory experience that can actively engage students in learning. Through direct activities with real objects, students can more easily understand the relationship between parts and the whole, and construct a more meaningful understanding of equivalent fractions. In addition, the use of concrete media can create a contextual, fun, and interactive learning atmosphere, thereby encouraging learning motivation and increasing student engagement in the learning process. The findings of this study confirm that concrete media functions beyond mere aids, but rather as a learning strategy appropriate to the cognitive developmental characteristics of elementary school students. By using concrete media, teachers can facilitate more effective learning, build mathematical concepts gradually, and reduce students' misconceptions regarding fractions.